Vaccine court : the law and politics of injury - Kirkland, Anna (Anna Rutherford) (New York : New York University Press, 2017)
In 'Vaccine Court', Anna Kirkland tells the story of how a special no-fault compensation court in the United States handles very controversial claims that a vaccine has harmed someone.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2017).
Keywords: United States. -- Court of Federal Claims. -- Office of Special Masters; Vaccination -- Law and legislation -- United States; Vaccination -- Political aspects -- United States; Vaccination -- Complications -- United States; Products liability -- Vaccines -- United States; Law; Laws of specific jurisdictions & specific areas of law